Problem-solving and posing skills in middle school students: The impact of gender, school type and grade level - Mustafa Güler; Erdem Çekmez (Journal of Pedagogical Research, 2023)
This paper examined the problem-solving and problem-posing skills of middle school students in terms of whether the factors of gender and school type have an impact, as well as to illustrate these skills with respect to grade levels. A total of 461 students from different middle school levels of both private and public schools participated in the study. The instrument and framework reported by Cai (2003) were applied in the data collection and analysis phases of the study. The results revealed no significant differences between private and public schools in terms of problem-solving and problem-posing skills. In terms of gender, similar characteristics were found in terms of problem-solving skills, while differences in problem-posing skills were noted. In addition, some differences were observed in terms of problem-solving and problem-posing skills according to grade level. These results are discussed in the context of the existing literature.